COVID-19 Pandemic and Violence Against Children - Aris Tristanto (Indev: Literasi Media Dakwah dan Pengembangan Masyarakat, 2024)
During the COVID-19 pandemic, it was known that number violence to child in Indonesia more increase. Study this is study References with objective for study reason happening violence against children During the COVID-19 pandemic and effort in prevention. Factor common causes of hard cake  on children during the COVID-19 pandemic is a problem economy as a result of activity restrictions during pandemic, the relationship between children and parents who are not balanced, and low parental knowledge related with parenting patterns. Impact period short of perceived violence children is to affect the child 's physical, while the impact long-term related to the psyche of the victim. In overcoming, The problem of violence against children during the COVID-19 pandemic must be carried out in a social environment with various preventive measures. On In this research, the author suggests there needs to be awareness, that acts of violence against children are extraordinary crimes that can interfere with the growth and development of children.